Searching for deviations from the general relativity theory with gas mass fraction of galaxy clusters and complementary probes - Holanda, R. F.L.; Pereira, S. H. [UNESP]; Santos Da Costa, S. (American Physical Society (APS), 2017)
Nowadays, thanks to the improved precision of cosmological data, it has become possible to search for deviation from the general relativity theory with tests on large cosmic scales. Particularly, there is a class of modified gravity theories that breaks the Einstein equivalence principle (EEP) in the electromagnetic sector, generating variations of the fine structure constant, violations of the cosmic distance duality relation, and the evolution law of cosmic microwave background (CMB) radiation. In recent papers, this class of theories has been tested with angular diameter distances from galaxy clusters, type Ia supernovae, and CMB temperature. In this work we propose a new test by considering the most recent x-ray surface brightness observations of galaxy clusters jointly with type Ia supernovae and CMB temperature. The crucial point here is that we take into account the dependence of the x-ray gas mass fraction of galaxy clusters on possible variations of the fine structure constant and violations of the cosmic distance duality relation. Our basic result is that this new approach is competitive with the previous one, and it also does not show significant deviations from general relativity.